Assay of Phthalic Anhydride and Some Related Compounds by Volumetric Methods - Dubey, P.K.; Ghouse Mohiuddin, S.M.; Ramesh, D. (Asian Journal of Chemistry, 2010)
Three simple methods are described for the assay of phthalic anhydride. The first method involves titration of a methanolic solution of phthalic anhydride with standardised methanolic alkali. In the second method, phthalic anhydride is hydrolysed with boiling water, subsequently titrated with standardised aq. alkali. In the third method, phthalic anhydride is treated with a large excess of aq. alkali and the unconsumed alkali is titrated against standardised aq. acid (back-titration method). All the three methods are comparable and give good results.